2023
DOI: 10.7759/cureus.34429
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma and Differentiated Thyroid Cancer: A Case Series

Abstract: Occurrences of lymphoma and differentiated thyroid cancer are rare. Usually, involvement of the thyroid gland is seen as a part of extranodal involvement or as a part of radiation-induced malignant transformation in previously treated lymphoma patients. The incidence of synchronous hematological malignancy with differentiated thyroid cancer is 7%. The synchronous occurrence of differentiated thyroid cancer and lymphoma poses a significant diagnostic and treatment dilemma. Here we report a case series of four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The results of the study revealed that genetic modifications significantly enhanced the prognosis‐free survival of those diagnosed with cancer (Figure 3D). Additionally, growing research in recent years has shown a strong link between DNA methylation and the development of cancer 17 . DNA methylation may play a significant role in the epigenetic regulation of cancer cell proliferation, invasion, differentiation and death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study revealed that genetic modifications significantly enhanced the prognosis‐free survival of those diagnosed with cancer (Figure 3D). Additionally, growing research in recent years has shown a strong link between DNA methylation and the development of cancer 17 . DNA methylation may play a significant role in the epigenetic regulation of cancer cell proliferation, invasion, differentiation and death.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, growing research in recent years has shown a strong link between DNA methylation and the development of cancer. 17 DNA methylation may play a significant role in the epigenetic regulation of cancer cell proliferation, invasion, differentiation and death. The methylation status of several genes has emerged as a crucial prognostic indicator for tumour prognosis.…”
Section: Resultsmentioning
confidence: 99%